Ultrasound-promoted Organic Synthesis - A Recent Update - Brahmachari, Goutam; Nayek, Nayana; Mandal, Mullicka; Bhowmick, Anindita; Karmakar, Indrajit (Current Organic Chemistry, 2021)
Abstract: Ultrasonication, nowadays, is well-regarded as an effective green tool in implementing a plethora of organic transformations. The last decade has seen quite useful applications of ultrasound irradiation in synthetic organic chemistry. Ultrasound has already come out as a unique technique in green chemistry practice for its inherent properties of minimizing wastes and reducing energy and time, thereby increasing the product yields with higher purities under milder reaction conditions. The present review summarizes ultrasound-promoted useful organic transformations involving both carbon-carbon and carbon-heteroatom (N, O, S) bond-forming reactions in the absence or presence of varying catalytic systems, reported during the period 2016-2020.
Keywords: energy-efficiency